The prevalence of smoking and its associated factors among military personnel in Kingdom of Saudi Arabia: A national study - Hesham I Al-Khashan; Fahad S Al Sabaan; Hifa S Al Nasser; Ahmed A Al Buraidi; Ahmed D Al Awad; Ghalib B Horaib; AlJoharah H Al Obaikan; Adel M Mishriky (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim was to measure the prevalence of smoking and identify its potential predictors among military personnel in Kingdom of Saudi Arabia (KSA). Materials and Methods: This cross-sectional study was carried out among military personnel in the five military regions of KSA between January 2009 and January 2011. The sample of 10,500 military personnel in the Saudi Armed Forces was equally divided among the five regions with a ratio 3:7 for officers and soldiers. A multistage stratified random sampling was used to recruit participants in the four services of the armed forces in the five regions. Information on sociodemographic characteristics with a detailed history of smoking was collected by means of a self-administered questionnaire. Bivariate analysis was used to identify the factors associated with smoking, and multiple logistic regression analysis to discover its potential predictors. Results: About 35% of the sample was current smokers, with higher rates among soldiers. The eastern region had the highest rate (43.0%), and the southern region the lowest (27.5%). Navy personnel had a higher risk of being current smokers (40.6%), and the air defense the lowest risk (31.0%). Multivariate analysis identified working in the navy, and low income as positive predictors of current smoking, while residing in the southern region, older age, years of education, being married, and having an officer rank were negative (protective) factors. Conclusion: Smoking is prevalent among military personnel in KSA, with higher rates in the Navy and Air Force, among privates, younger age group, lower education and income, and divorced/widowed status. Measures should be taken to initiate programs on smoking cessation that involve changes in the environment that is likely to promote this habit.